Tafsir Al-Isyari - Nana Mahrani (Sekolah Tinggi Agama Islam Sumatera Medan, 2017)
Tafsir isyari is one type of interpretation for explaining the verses of the Qur'an thick with takwil, esoteric aspects and cues contained in the text of the verses of the Qur'an. Despite the controversy that occurred in commenting on this kind of interpretation, which clearly isyari interpretation is a form of contribution of scholars in literature pembendaharaan enriching interpretation as well as expanding the understanding of the meaning of the Qur'an. Ala kulli things isyari commentators have given a distinctive color in the discourse of commentary from time to time.